(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article examines the issues of substantive redesigning physics based on a competency-based approach in the development of engineering abilities in students studying in the field of construction engineering. The necessity of integrating the physics course with engineering activities, the principles of forming the content, the analysis of modules, the strategies used in the educational process, and the criteria for developing students’ professional competencies were scientifically investigated.